2022
DOI: 10.1177/2455328x211063068
|View full text |Cite
|
Sign up to set email alerts
|

Gender Matters: Reappraising the Issues of Equity, Participation and Ownership in Watershed Management

Abstract: Equal share in governance of managing natural resources is one of the strategic aspects of neoliberal developmentalism. Additionally, this process of natural resource governance (NRG) considers communities as a homogeneous entity by ignoring the cultural politics of gender division to maintain the latency and equilibrium of the existing gendered order and regime. Watershed developmental project is no exceptional in this regard. The existing empirical literature shows that the gender governance (GG) issues in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…There were also two groups of SCs 7 in Parasai; one of these groups has closer ties to the gadhiwale Yadav community and has greater access to resources. The observed processes of local political negotiations, social inclusion and social exclusion in the integrated watershed management projects reflect similar findings elsewhere in India (Adolph & Turton, 1998;Dash et al, 2011;Kale, 2011;Kumar & Kumar, 2022).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…There were also two groups of SCs 7 in Parasai; one of these groups has closer ties to the gadhiwale Yadav community and has greater access to resources. The observed processes of local political negotiations, social inclusion and social exclusion in the integrated watershed management projects reflect similar findings elsewhere in India (Adolph & Turton, 1998;Dash et al, 2011;Kale, 2011;Kumar & Kumar, 2022).…”
Section: Resultssupporting
confidence: 83%
“…For women, reasons such as not being taken seriously in the meetings, inconvenient timings of the meetings and lack of information about the meeting are prominent across the villages. The patriarchal structure of the villages also became evident with the finding that about 11.4% of women in Chhatpur and 10.2% in Parasai could not attend the meetings due to lack of support from family members (Kumar & Kumar, 2022;Saxena & Singh, 2014 Women participants from non-dominant communities particularly believed that their concerns were not adequately addressed either in the WC or village association meetings. One of the key informants from Bacchauni village observed that a part of her family landholding is submerged under water after the construction of the watershed until the festival of Deepawali in November.…”
Section: Resultsmentioning
confidence: 99%